Optimal Scan Time of 18F-FDG PET in Identifying Therapeutic Efficacy Secondary to Radiofrequency Ablation of Lung Cancer. Issue 24 (June 2015) - Zhang, Wen-Qian; Fu, Yi-Li; Hu, Bin; Chen, Shuo; Yang, Min-Fu; Li, Hui; Lawen., Alfons
<x xml:space="preserve">Abstract</x> Abstract Positron emission tomography (PET)/computed tomography (CT)–guided radiofrequency ablation (RFA) has become a major treatment approach for small tumors. Identifying this quantitative dynamic 18F-2-fluoro-2-deoxy-d-glucose (18F-FDG) activity at the primary lesion can minimize misdiagnosis and allow an opportunity to reintervene. Here, we report 3 patients with nonsmall cell lung cancer (NSCLC) who underwent the ablative therapy with split-dose 18F-FDG fused PET/CT scans for early identification of residual tumors and follow-up evaluation of treatment. Our results indicate that reliable post-RFA imaging follow-up is critical in fast and efficient assessment of complete tumor resection in patients experienced the ablation procedure.